2016
DOI: 10.1016/j.poly.2015.10.059
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent coordination polymers of 2,2′-bipyrimidine and mercury(II) salts: A structural and computational study

Abstract: We report the synthesis and structural, thermal and vibrational characterization of five complexes of the 2,2'bipyrimidine (bipym) with HgX 2 , X=Cl, Br, I, CN, SCN, with the aim to investigate the factors that could influence the supramolecular chemistry of mercury(II). The combination of the 2,2'-bipym ligand, a bidentate molecule, and bridging anions together with a d 10 metal like mercury(II) has given different polymeric structures with 1D and 3D dimensionality. A computational modelling, compared to stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 120 publications
1
8
0
1
Order By: Relevance
“…It has been demonstrated that upon moving from the chloride to the iodide, the bridging behaviour is reduced and the bridging interactions are weaker. 28 In the case of bpy complexes, the chloride forms a true 1D-coordination polymer, 18 while the bromide and iodide form dimers that interact through spodium bonding, 50 giving dimeric molecular entities 19 and very weakly interacting dimers, 20 respectively. The packing of 2 is an intermediate between that of bromide and iodide: very long spodium bonding interactions connect the molecules of the dimers, at the edge of the VdW sum ( d (Br/I⋯Hg) = 3.404(8) Å and 3.377(8) Å, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that upon moving from the chloride to the iodide, the bridging behaviour is reduced and the bridging interactions are weaker. 28 In the case of bpy complexes, the chloride forms a true 1D-coordination polymer, 18 while the bromide and iodide form dimers that interact through spodium bonding, 50 giving dimeric molecular entities 19 and very weakly interacting dimers, 20 respectively. The packing of 2 is an intermediate between that of bromide and iodide: very long spodium bonding interactions connect the molecules of the dimers, at the edge of the VdW sum ( d (Br/I⋯Hg) = 3.404(8) Å and 3.377(8) Å, respectively).…”
Section: Resultsmentioning
confidence: 99%
“…For example, in [(CuI) 2 (bpym)], 13a the rhombus-shaped Cu 2 I 2 motifs could be bridged by the bpym ligands leading to a chain, in which the cable of two bridged iodine is perpendicular to bpym plane (Figure S4a,b). In [Hg 2 I 4 (bpym)], 16 the dimeric Hg 2 I 4 fragments with two different orientations are interconnected by bpym ligands to form an infinite chain (Figure S4c). The dihedral angle between dimeric metal halide plane (Hg 2 I 2 ) and bpym plane is 53.11°, which is smaller than that of 1 (70.05°) and 2 (74.80°) (Figure S4d).…”
Section: ■ Experiments Sectionmentioning
confidence: 99%
“…This is similar to [Hg 2 I 4 (bpym)] whose absorption is calculated to be the charge-transfer from inorganic moiety I to bpym. 16 Therefore, the band edge absorption around 375 nm should arise from the inorganic moiety (i.e., Bi and Cl) to organic ligand (bpym) chargetransfer (IOCT), in which the main contribution is from Cl to bpym, namely, interligand LLCT. The bandgaps of 1 and 2 are calculated to be indirect 2.501 and 2.481 eV, respectively.…”
Section: ■ Experiments Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Их применяют для создания светодиодов и светящихся дисплеев [1,2], для технического анализа и контроля качества [3,4]. Ведутся работы по фундаментальным исследованиям люминесцентных полимерных композиций [5][6][7].…”
Section: Introductionunclassified